Answer:
A) ( -7,-2)
Explanation:
-3x + 6y = 9 ⇒ multiply by 5⇒(5) -3x + (5)6y = (5)9 ⇒ -15x + 30y = 45
5x + 7y = -49 ⇒ multiply by 3⇒3(5x) + (3) 7y = (3) -49 ⇒15x + 21y = -147
Add the two bold equations together and solve for y
15x + 30y = 45
-15x + 21y = -147
51y = -102 Divide both sides by 51
=
![(-102)/(51)](https://img.qammunity.org/2023/formulas/mathematics/high-school/jxav7w207rkjiytn10j1r3pqep4b92uqzb.png)
y = -2
Substitute -2 into either of the two original equation to solve for x.
-3x + 6y = 9
-3x + 6(-2) = 9
-3x - 12 = 9 Add 12 to both sides
-3x -12 + 12 = 9 + 12
-3X = 21 Divide both sides by -3
=
![(21)/(-3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ctnzowu63aq3rkshmbfgya17tlm0111mxk.png)
x = -7
Solution: (-7, -2)
Check:
-3x + 6y = 9
-3(-7) + 6(-2) = 9
21 -12 = 9
9 = 9 checks
5x + 7y = -49
5(-7) + 7(-2) = -49
-35 -14 = -49
-49 = -49 Checks